Influence des solvants aromatiques sur les propriétés optiques du bleu de phtalocyanine de cuivre en milieu pictural - Catherine Defeyt (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
Currently, five forms of copper phthalocyanine blue, PB15, :1, :2, :3, :4, and :6, are used as artistic pigments. PB15, the most widespread form afterwards PB15:3 is prone to crystallisation. This phenomenon changes the metastable α form into a coarsely crystalline form with an attendant loss of tinctorial strength. Crystal growth can occur in many media but is most often seen in paints containing aromatic solvents. The use of aromatic solvents as part of conservation treatments of paintings is relatively common. For example, the toluene and  the xylenes found in  lining adhesives (as Beva 371), of some types varnish (as Laropal A81), and several mix of solvents used for cleaning or removal of the varnish. In conclusion, a search must be undertaken to determine if the conditions of use of aromatic solvents in conservation involves the crystallisation of PB15.In this paper  we will present the first results corresponding to the study of PB15, :1, :2, :3, :4, :6. These fives forms have been examined by polarized light microscopy and analysed with Fourier transform IR spectroscopy and X ray diffraction  in order to compare optical and chemical properties before and after they have been in contact with aromatic solvents.